Presence of Porphyromonas gingivalis in esophagus and its association with the clinicopathological characteristics and survival in patients with esophageal cancer. Issue 1 (December 2016) - Gao, Shegan; Li, Shuoguo; Ma, Zhikun; Liang, Shuo; Shan, Tanyou; Zhang, Mengxi; Zhu, Xiaojuan; Zhang, Pengfei; Liu, Gang; Zhou, Fuyou; Yuan, Xiang; Jia, Ruinuo; et al.
Abstract Background Mounting evidence suggests a causal relationship between specific bacterial infections and the development of certain malignancies. However, the possible role of the keystone periodontal pathogen, Porphyromonas gingivalis, in esophageal squamous cell carcinoma (ESCC) remains unknown. Therefore, we examined the presence ofP. gingivalis in esophageal mucosa, and the relationship betweenP. gingivalis infection and the diagnosis and prognosis of ESCC. Methods The presence ofP. gingivalis in the esophageal tissues from ESCC patients and normal controls was examined by immunohistochemistry using antibodies targeting whole bacteria and its unique secreted protease, the gingipain Kgp. qRT-PCR was used as a confirmatory approach to detectP. gingivalis 16S rDNA. Clinicopathologic characteristics were collected to analyze the relationship betweenP. gingivalis infection and development of ESCC. Results P. gingivalis was detected immunohistochemically in 61 % of cancerous tissues, 12 % of adjacent tissues and was undetected in normal esophageal mucosa. A similar distribution of lysine-specific gingipain, a catalytic endoprotease uniquely secreted byP. gingivalis, andP. gingivalis 16S rDNA was also observed. Moreover, statistic correlations showedP. gingivalis infection was positively associated with multiple clinicopathologic characteristics, including differentiation status, metastasis, and overall survival rate. Conclusion These findings demonstrate for the first time thatP. gingivalis infects the epithelium of the esophagus of ESCC patients, establish an association between infection withP. gingivalis and the progression of ESCC, and suggestP. gingivalis infection could be a biomarker for this disease. More importantly, these data, if confirmed, indicate that eradication of a common oral pathogen could potentially contribute to a reduction in the overall ESCC burden.